Managing differences : a guide to proactive management skills - McArdle, Geri (Crisp Pub. MenloUS, 1995)
Provides practical negotiation and persuasion techniques for managing/resolving differences. Identifies sources of differences and suggests five styles for managing them. Explains the negotiation process.